Dakwah Dengan Seni Musik: Studi Pada Grup Qosidah Modern At-Tarbiyah Putri Cilendek Cibeureum Kota Tasikmalaya - Hanif Fuadi, Muhamad; Alfarisi, Salman (IAIN Madura, 2023)
The purpose of this research is to reveal the phenomenon of da'wah with the art of music as a means to attract mad’u, especially young people. Da'wah and music are both mutually beneficial. Da'wah as an effort to call for goodness while the art of music makes beauty in calling for goodness. The progress of the times is a step to innovate in the development of da'wah, in music the lyrics as a means of propaganda, young people as targets of propaganda even for group personnel to become a means of propaganda in the field of economic empowerment. This study uses qualitative methods as an effort to reveal the meaning behind the establishment and activities from stage to stage of the Qasidah Group. Field observations, in-depth interviews and documentation became the material for analysis in this study. The results of this study reveal innovation in da'wah namely packaging messages of aqidah, Sharia and morals with music, the basis of religious education from Islamic boarding schools as a philosophy in concocting da'wah messages in music, enthusiastic young people who see appearances on stage as an internalization of Islamic values, then this group becomes a means for economic empowerment of its members so that they can support their families from every stage to stage.